2012
DOI: 10.5045/kjh.2012.47.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of granulocyte-colony stimulating factor and the expression of its receptor on various malignant cells

Abstract: BackgroundGranulocyte-colony stimulating factor (G-CSF) is extensively used to improve neutrophil count during anti-cancer chemotherapy. We investigated the effects of G-CSF on several leukemic cell lines and screened for the expression of the G-CSF receptor (G-CSFR) in various malignant cells.MethodsWe examined the effects of the most commonly used commercial forms of G-CSF (glycosylated lenograstim and nonglycosylated filgrastim) on various leukemic cell lines by flow cytometry. Moreover, we screened for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Moon et al [ 28 ] were the first to reveal proliferation and differentiation in leukemia and solid tumor cells using 38 solid tumor cell lines and five hematopoietic cell lines. They found that G-CSF stimulated proliferation (40%-80% increase in proliferation in treated cells compared with that in control cells) in three leukemic cell lines and induced differentiation of AML1/ETO+ leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moon et al [ 28 ] were the first to reveal proliferation and differentiation in leukemia and solid tumor cells using 38 solid tumor cell lines and five hematopoietic cell lines. They found that G-CSF stimulated proliferation (40%-80% increase in proliferation in treated cells compared with that in control cells) in three leukemic cell lines and induced differentiation of AML1/ETO+ leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…That necessitates their consideration in a differential diagnosis given the use of adjuvant GM‐CSF in these patients . Melanoma cells in vitro have been found to express G‐CSFR transcript; increases in cell proliferation, however, do not occur upon G‐CSF stimulation possibly reflecting an absence of a G‐CSFR protein . In contrast, a role of GM‐CSF in dissemination of melanoma is controversial.…”
Section: Tumors Secreting G‐/gm‐csfmentioning
confidence: 99%
“…G-CSF is known to induce proliferation in various cell types via G-CSF-R, and different signal-transduction pathways can be induced depending on the different binding sites of G-CSF-R [21]. The Jak-Stat pathway is one signaling pathway that regulates cell proliferation by G-CSF via G-CSF-R [9][10][11]. We analyzed the effect of G-CSF on the mRNA-expression level of suppressor of cytokine signaling (SOCS)-3, which is a negative regulator of G-CSF-R and down-regulates G-CSF signaling [22].…”
Section: Mitogen-activated Protein Kinase (Mapk) Signalsmentioning
confidence: 99%
“…The mRNA-expression levels of ER in both cell lines did not show any significant difference in any group (Figure 4C, 4F). G-CSF can induce cell proliferation in many normal cell types (including normal chorionic cells) and in cancer cells [9,11]. In contrast, the only report showing that G-CSF suppressed cell proliferation was performed with BeWo (culture condition: 2.5-10% serum) and JEG-3 (2.5% serum) human choriocarcinoma cells (half-maximal effect of G-CSF observed at 30-50 ng/ml) [13] in agreement with the present report (however, Marino et al showed that JEG-3 cell proliferation increased after administration of 1 g/ml  of G-CSF in culture medium containing 0.5% serum [14]).…”
Section: Pr and Er Mrna Appearancementioning
confidence: 99%
See 1 more Smart Citation